Practice makes practice : a critical study of learning to teach - Britzman, Deborah P., 1952- (Teacher empowerment and school reform., 2003)
In this ethnographic study contributing to the discourse on what teaching does to teachers, Britzman (education, social and political thought; women's studies, York U., Toronto) explores the meaning of their often contradictory experiences through secondary teacher narratives. This edition (no date.